Specific immune response of oral administration of Dahi and milk fermented with Lactobacillus helveticus against Salmonella enteritidis in mice - Meena, Kamalesh Kumar (Indian Journal of Dairy Science, 2017)
The aim of the study was to evaluate specific immune response of milk fermented with Lactobacillus helveticus and its cell free supernatant as compare to Dahi (Curd). In order to confirm specific immune response of those products an in-vivo study was conducted using mice as an animal model and the mice was challenged with Salmonella enteritidis infection. The immune response in those mice was assessed by analysing secretary immunoglobulin-A in the intestinal fluid at 2, 5 and 8th day post-challenge by ELISA method and colonization of pathogen (Salmonella enteritidis) in intestine (large and small), liver, and spleen. It was observed that level of secretary Immunoglobulin (Ig-A) response was maximum on 5th day after feeding of all three products. In colonization assay study there was reduction observed in colonization of Salmonella enteritidis in intestine (small and large), liver and spleen and the maximum reduction occurred on 8th day post challenge. The challenge studies showed protective and immune stimulatory potential of those three fermented product against infection of Salmonella enteritidis. It was also observed that Humoral/specific immune response of Lb. helveticus-fermented milk and its cell free supernatant was as significant as Dahi.